The Impact of the Malaria Parasite on Global Health - Omar Khalel Rajab; Ali Thajeel Muttair; Jaber Rashid Wannas; Qasim Mohammed Abdul Amir (American Journal of Biology and Natural Sciences, 2024)
Malaria is an acute, chronic, and disabling parasitic disease accounting for millions of deaths and huge amounts of suffering in the human population yearly. Around 3.2 billion people are currently at risk of infection from Plasmodium parasites. Despite the promising advances of recent years in research and public health addressing malaria control, this disease remains one of the main health concerns in developing countries. In this review, we outline some of the key peculiarities of malaria, including epidemiology, biological aspects of the malarial parasite, host responses to malaria infection, and also discuss the clinical manifestations associated with the parasite. We also highlight the current strategies for disease control, before conveying how this often dismissive or short-sighted approach of many campaigns results in many health and social consequences for a large proportion of the world’s population. This paper aims to give an outline of knowledge regarding malaria thus far and key future research directions in regard to both the parasite and its current control strategies. It gives a clear view of what we already know regarding epidemiology, biology, and clinical symptoms resulting from the malaria parasite, and the many knowledge gaps still existing that hinder further understanding of the malarial infection and block possible future new treatments and interventions against the disease.